The Relationship Between the Expression of Resistin and Apoptosis Factors in Placenta and the Pathogenesis of Gestational Diabetes Mellitus - Jun Yu; Xiao-Ling Su; Jing Jia; Yu Zeng; Jing-Yi Zhang; Shao-Shuai Wang; Ling Feng; Yang Pan; Dan-Dan Shi (Wolters Kluwer Health, 2020)
Abstract. Objective:. To detect the expression of caspase-3, baculoviral inhibitor of apoptosis repeat containing 5 (BIRC-5), vascular endothelial growth factor (VEGF), hypoxia-inducible factor (HIF), and the concentration of resistin protein in placental of patients with gestational diabetes mellitus (GDM) and normal pregnant women, and to explore its correlation with the pathogenesis of GDM and its significance. Methods:. This study includes 30 pregnant women who chose cesarean section at Tongji Hospital of Tongji Medical College during May 2013 to February 2014: 15 GDM patients and 15 normal glucose tolerance patients. The expression of caspase-3, VEGF, HIF, and BIRC-5 in placenta of 15 patients with GDM (GDM group) and 15 normal late pregnancy (control group) was detected by real-time fluorescence quantitative polymerase chain reaction. The concentration of resistin protein in the placenta was detected by enzyme-linked immunosorbent assay. Results:. Compared with the control group, the expression of caspase-3, HIF, VEGF, resistin in placenta of GDM group increased significantly (P < 0.05); the expression of BIRC-5 in placenta of GDM group decreased significantly (P < 0.05). Conclusion:. The expression of caspase-3, BIRC-5, VEGF, HIF, and resistin in placenta of GDM patients and normal pregnant women are significantly different, which may be involved in the pathogenesis of GDM disease.